The financial and economic challenges of housing provision for an ageing society. Issue 2 (1st August 2016) - Ruddock, Les; Ruddock, Steven
Abstract : Purpose: The purpose of the paper is to assess the critical financial and economic issues associated with the provision of adequate housing in the UK in the face of current and future demographic change. Design/methodology/approach: The review is based on an investigation of the current state of preparedness of the housing market and its various stakeholders based on recent reports and secondary statistical evidence. Findings: The findings emphasise the need for a multi-faceted approach to tackle the challenges that need to be addressed. Unless measures are initiated to influence the market, the requisite increase in the stock of appropriate housing in the face of rapid demographic change will not occur. Originality/value: The value of the study is that it identifies the issues based on the current state of provision and makes recommendations for meeting the challenges arising from these issues. These recommendations have strong implications for policymakers and other stakeholders.